BRAND IMAGE MEMEDIASI KUALITAS PRODUK DAN HARGA DENGAN KEPUTUSAN PEMBELIAN SMARTPHONE APPLE DI KOTA DENPASAR - Saraswati, Agung Ratih; Rahyuda, I Ketut (E-Jurnal Manajemen; Vol 6 No 6 (2017), 2017)
The purpose of this study was to determine the Mediating Role of Brand Image and Perception of Product Quality Price with Apple Smartphone Product Purchasing Decisions in Denpasar. This study is associative and do in the city of Denpasar. The sample in this study amounted to 119 people with sampling.Teknik purposive method of data analysis is done by using path analysis (path analysis) and Sobel test with SPSS for windows. The results of this study indicate that the quality of the product and the price of each positive and significant effect on the brand image. Brand image, product quality, and price of each positive and significant impact on purchasing decisions. Brand image positively and significantly mediate product quality and price with the purchase decision. product quality, price, brand image and purchase decision Normal 0 false false false EN-GB X-NONE X-NONE
Keywords: product quality, price, brand image and purchase decision